2021
DOI: 10.1097/cu9.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antimuscarinic drugs to beta adrenergic agonists in overactive bladder: A literary review

Abstract: Background: The purpose of this study was to carry an extended literature review to compare antimuscarnics with beta adrenergic agonists (mirabegron) in treatment of overactive bladder. Materials and methods: A literature review was carried out, using key words in different databases including MEDLINE, PUBMED, and EMBASE. All relevant published articles during last 5 years with full texts available were included in this review for critical analysis and evaluation. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Wani et al (15) revealed that nine research examined the efficacy of these two classes of drugs in their meta-analysis. According to the findings of all the trials, mirabegron is just as effective as any other anticholinergic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wani et al (15) revealed that nine research examined the efficacy of these two classes of drugs in their meta-analysis. According to the findings of all the trials, mirabegron is just as effective as any other anticholinergic.…”
Section: Discussionmentioning
confidence: 99%
“…Wani et al (15) indicated that five studies analyzed the negative effects of both treatments in their metaanalysis and found that mirabegron has less side effects than antimuscarinics.…”
Section: Discussionmentioning
confidence: 99%